Three colorimetric and off–on fluorescent chemosensors for Fe3+ in aqueous media. (4th March 2013) - Chai, Meimei; Li, Man; Zhang, Di; Wang, Cui‐cui; Ye, Yong; Zhao, Yufen
ABSTRACT: Three Rhodamine B derivatives were synthesized and characterized by ESI‐MS, NMR, HR‐MS and IR. The probes exhibit high selectivity and sensitivity towards Fe 3+ over other metal ions in CH3 CN–water. Upon the addition of Fe 3+, the spirocyclic ring of the probe was opened and a significant enhancement of visible color and fluorescence within the range of 540–700 nm was observed. The colorimetric and fluorescent response to Fe 3+ can be conveniently detected even by the naked eye, which provides a facile method for the visual detection of Fe 3+ . Job's plot, fluorescence titration and MS indicated the formation of 1:2 complexes between the probes and Fe 3+ . The reversibility of the reaction establishes the potential of these probes as chemosensors for Fe 3+ detection. Copyright © 2013 John Wiley & Sons, Ltd.